PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN DAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING(Studi Pada Konsumen Sabana Fried Chicken Di Universitas Bhayangkara Jakarta Raya) - Hibatullah, Hazza; Sawitri, Ni Nyoman; Navanti, Dovina (SINERGI : Jurnal Riset Ilmiah, 2025)
The Effect of Brand Image and Product Quality on Consumer Purchase Interest and Consumer Satisfaction as Intervening Variables (Study on Sabana Fried Chicken Consumers at Bhayangkara University, Greater Jakarta).The purpose of this study was to investigate the effect of brand image and product quality on consumer buying interest and consumer satisfaction as an intervening variable. The research method used is quantitative research method, with the type and source of primary data obtained from distributing questionnaires. The population and sample of this study were respondents who had bought or consumed Sabana Fried Chicken. The sampling technique used was purposive sampling technique, resulting in 170 data samples that met the criteria. The analysis method used is descriptive statistical test, outer model test, inner model test, and hypothesis testing. The results of this study indicate including: 1) Brand image affects customer satisfaction; 2) Brand image affects purchase intention; 3) Product quality affects consumer satisfaction; 4) Product quality has no effect on purchase intention; 5) Purchase intention affects customer satisfaction; 6) Brand image affects purchase intention through customer satisfaction; 7) Product quality affects purchase intention through customer satisfaction